Efficacy and safety of Run Zao Zhi Yang capsule on chronic eczema: a multiple-center, randomized, double-blind, placebo-controlled clinical study. (3rd October 2019) - Huang, Dan; Chen, Kun; Zhang, Fu-Ren; Yang, Sen; Guo, Qing; Xu, Jin-Hua; Li, Hui; Tan, Guo-Zhen; Yang, Bao-Qi; Lu, Qian-Jin; Zheng, Jie; Li, Lin-Feng; et al.
Abstract: Background: Run Zao Zhi Yang capsule (RZZYC) has been widely applied for eczema treatment as a traditional Chinese medicine, while its efficacy has not been scientifically investigated. Objective: We conducted this multiple-centers, randomized, double-blind, placebo-controlled study to investigate the effectiveness and safety of RZZYC on the treatment of patients with mild to moderate chronic eczema. Methods: 240 patients were randomly assigned into the experimental group and the placebo group. The primary efficacy indicator was the Eczama Area and Severity Index (EASI) score at week 4. The patient with an EASI score that decreases more than 95% from baseline (EASI 95) was judged as cured. The cured patients were followed up for another 8 weeks. The differences on EASI, Visual Analogue Score (VAS), and Dermatology Life Quality Index (DLQI) score were compared. Results: The proportions of EASI 95 and EASI 60 in the experimental group were significantly higher than those of the control group at week4 ( p  = .002 and p  < .001, respectively), the VAS score decreased more significantly in the experimental group at week 4. After 8 weeks follow-up, no difference on recurrence rate and adverse event rate between the two groups was observed. Conclusion: RZZYC provides a good effect on the treatment of mild-to-moderate chronic eczema with a low recurrence and tolerable adverse events, and is a potential treatment that may be implemented in clinical practice.